1991
DOI: 10.1128/aac.35.8.1635
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas pseudomallei resistance to beta-lactam antibiotics due to alterations in the chromosomally encoded beta-lactamase

Abstract: Pseudomonas pseudomallei, the causative agent of melioidosis, is generally susceptible to some of the newer extended-spectrum cephalosporins or to combinations of a ,-lactam and clavulanic acid, a ,-lactamase inhibitor. Resistance to these agents may, however, emerge during treatment. We report on alterations in the chromosomal D-lactamase associated with the development of resistance. Three resistance patterns resulted from three different mechanisms in the strains investigated. Derepression of the chromosoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 37 publications
(51 reference statements)
0
36
0
Order By: Relevance
“…Functionally, the most important of these is the BushJacoby-Medeiros class 2e beta-lactamase BPS-1, encoded by the gene blaA (or penA; Ambler class A), which hydrolyzes most cephalosporins but is readily inhibited by clavulanate (91,274). Acquired resistance to beta-lactam antibiotics while on treatment with a beta-lactam-beta-lactamase inhibitor combination or ceftazidime resulted from three distinct phenotypic changes: derepression of the chromosomal enzyme, an insensitivity to inhibition by beta-lactamase inhibitors, and a betalactamase specific for ceftazidime (169). These were associated with mutations in the blaA gene (439).…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…Functionally, the most important of these is the BushJacoby-Medeiros class 2e beta-lactamase BPS-1, encoded by the gene blaA (or penA; Ambler class A), which hydrolyzes most cephalosporins but is readily inhibited by clavulanate (91,274). Acquired resistance to beta-lactam antibiotics while on treatment with a beta-lactam-beta-lactamase inhibitor combination or ceftazidime resulted from three distinct phenotypic changes: derepression of the chromosomal enzyme, an insensitivity to inhibition by beta-lactamase inhibitors, and a betalactamase specific for ceftazidime (169). These were associated with mutations in the blaA gene (439).…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…The bacterial strains and plasmid used in this study are shown in Table 1. B. pseudomallei strains used in this study were collected from blood and urine samples from melioidosis patients both before and during antibiotic treatment at Sappasitprasong Hospital, Ubon Ratchatani, Thailand, between 1986 and 1989 and have been described previously (7,10). All bacterial strains were grown at 37°C on Luria-Bertani (LB) agar or in LB broth.…”
Section: Methodsmentioning
confidence: 99%
“…Livermore, et al described a clavulanic acid-inhibitable ␤-lactam resistance phenotype of B. pseudomallei (13), and recently, the cloning of B. pseudomallei class A and D ␤-lactamases has been reported (4,14). Godfrey et al described three different phenotypes of clinical isolates from three patients which had undergone antibiotic treatment, and demonstrated that the resistance was due to derepressed ␤-lactamase production and structural mutations in the enzyme (10). Here, we examine the B. pseudomallei penA gene encoding a class A ␤-lactamase in the clinical isolates of B. pseudomallei described by Godfrey et al and from B. mallei ATCC 23344.…”
mentioning
confidence: 99%
“…Treatment requires long and costly administration of antibiotics, and few antimicrobials are effective due to the intrinsic resistance of B. pseudomallei (2,23). The potential spread of acquired resistance (24,25) and the lack of any new promising drugs in development are ominous circumstances in regard to the future of melioidosis disease management. As generally only clinical symptoms are used for disease management, there is an unmet need for biomarkers that can help to monitor disease progression and guide antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%